Epicuticular Wax and Cuticular Resistance in Rice - O'Toole, J.C.; Cruz, R.T.; SEIBER, J.N. (Wiley, 1979)
High leaf cuticular resistance has been reported as a component adaptation of plants to drought prone regions, Experiments were conducted to evaluate and characterize the role of epicuticular wax as a component of cuticular resistance to water vapor loss from rice (Oryza sativa L.) leaves. This information is necessary to determine the applicability of including higher cuticular resistance in an upland rice breeding program and to evaluate potential selection methods.Diffusion porometry, electron microscopy, and gas liquid chromatography were employed. Measurement of cuticular resistance by leaf diffusive resistance porometry after stomatal closure by exposure of rice leaves to pure CO2 for 15 min was found sufficient to induce complete stomatal closure regardless of light level, and was superior to dark acclimation for this purpose.Removal of epicuticular wax from rice leaves by chloroform dip significantly reduced the cuticular resistance. Stressed plants were observed to increase cuticular resistance, illustrating the responsive nature of this characteristic.Gas liquid chromatography (GLC) of the chloroform leaf dip proved to be an expedient method of characterizing both quantitative and qualitative differences in the epicuticular wax of rice cullivars. The porometry and GLC techniques may be useful in selecting parents, spot checking in a pedigree program, or checking lines reaching the yield testing stage, but ate not well suited lor mass screening early generation progeny.Significant differences were found in the two rice cultivurs, ‘63–83′, an upland adapted rice from West Africa, and “IR20′, bred and selected in submerged paddy culture in ihc Philippines, by tlie above methods of characterizing cuticular resistance and epicuticular wax. These results are of ecological significance to plant breeders.